(untitled) (Journal of Contemporary Philology, 2020)
The goal of this paper is to analyse and understand the nature of the Legal English through the lexical and semantic relations of hyponymy and hypernymy present in the legal terms in English and Macedonian. From the analysis of the legal terms used in the criminal law, it can be concluded that the law vocabulary in English represents a clearly structured system of semantic fields which could be shown through the paradigmatic relations of hyponymy and hypernymy, starting from the archlexeme “law” (‘право’ in Macedonian), as a main hypernym, and many hyponyms which represent hypernyms of other hyperonyms, all up to the most basic terms in each separate semantic field. The term taxonym represents a hyponym of the term “hyponym”. This system is mainly characterised by the part/whole relationship, which holds not only between the individual lexemes and the lexical field, but also between the specific lexical fields and the vocabulary as a whole.